2019
DOI: 10.3390/nano9101400
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrothermal-Assisted Ball Milling Approach for Scalable Production of High-Quality Functionalized MoS2 Nanosheets for Polymer Nanocomposites

Abstract: The most known analogue of graphene, molybdenum disulfide (MoS2) nanosheet, has recently captured great interest because it can present properties beyond graphene in several high technological applications. Nonetheless, the lack of a feasible, sustainable, and scalable approach, in which synthesizing and functionalization of 2H-MoS2 nanosheets occur simultaneously, is still a challenge. Herein, a hydrothermal treatment has been utilised to reduce the effect of breaking mechanisms on the lateral size of produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 83 publications
(99 reference statements)
0
12
0
1
Order By: Relevance
“…Figure 1(b) displays the N 2 adsorption-desorption isotherms plots for BL-MoS 2 and BM-MoS 2 . As already discussed, BL-MoS 2 exfoliated into numerous layers, size of the particles, and thickness decreases, which afects the surface area of the MoS 2 [11,12]. Te higher surface area has a more active site, which can also increase the interaction of electrode and electrolyte; as a result, we have higher electrochemical performance [8].…”
Section: Bet Analysismentioning
confidence: 96%
“…Figure 1(b) displays the N 2 adsorption-desorption isotherms plots for BL-MoS 2 and BM-MoS 2 . As already discussed, BL-MoS 2 exfoliated into numerous layers, size of the particles, and thickness decreases, which afects the surface area of the MoS 2 [11,12]. Te higher surface area has a more active site, which can also increase the interaction of electrode and electrolyte; as a result, we have higher electrochemical performance [8].…”
Section: Bet Analysismentioning
confidence: 96%
“…This variety of forms can be controlled by choosing appropriate synthesis routes with optimized operational parameters. 17–33…”
Section: Molybdenum Sulfidementioning
confidence: 99%
“…19,40 In this context, Ahmadi et al demonstrated that a small amount of functionalized MoS 2 nanosheets (0.5% by weight) is sufficient to improve the mechanical properties of PS, PVA, and TPU, including tensile strength and Young's modulus. 19…”
Section: Molybdenum Sulfidementioning
confidence: 99%
“…Физические и химические свойства MoS 2 обусловливают его применение в катализе и нефтехимии [2,4]. При изготовлении катализаторов разделение на слои повышает дисперсность материла и, вследствие этого, увеличивает его удельную поверхность [5]. Кроме того, двумерный дисульфид молибдена имеет прямую запрещенную зону (E g ∼ 1.8 эВ), в отличие от массивного материала, который является непрямозонным полупроводником [6].…”
Section: Introductionunclassified